Optimisasi Keselamatan dan Kesehatan Kerja untuk Meningkatkan Produktivitas Tenaga Kerja - Hidayatulloh, Fajarshiddiq; Pasca, Yelsha Dwi (Journal of Innovation in Management, Accounting and Business, 2024)
Human resources are considered the most essential asset for any organization, encompassing a myriad of potential, skills, knowledge, and capabilities. Effective management of Human Resource Management (HRM) plays a crucial role in fostering a productive work environment. This study delves into the impact of workplace safety and health practices on employee productivity at PT. Shoetown Ligung Indonesia in Majalengka District.This quantitative research involved 99 respondents sampled from a workforce of 7,200 employees. The study utilized simple random sampling and employed various statistical analyses, including descriptive statistics, linear regression, correlation analysis, and hypothesis testing.The findings revealed that workplace safety, health practices, and productivity at PT. Shoetown Ligung Indonesia were rated moderately satisfactory based on the responses collected. Regression analyses demonstrated a positive and significant relationship between workplace safety and health practices individually with employee productivity. Moreover, the combined impact of both safety and health practices on productivity was notably substantial.However, the study highlighted that workplace safety, health practices, and productivity levels had not yet reached the expected 80% benchmark. This suggests areas requiring improvement in the workplace environment to elevate employee well-being and productivity.These results underscore the critical role of ensuring adequate workplace safety and health measures, indicating their direct influence on enhancing employee productivity. The study provides valuable insights into the significance of prioritizing safety and health measures within organizational strategies for achieving optimal productivity levels.